Situational and Dispositional Effects in Coping Assessment: An Application of the Latent State-Trait Theory - Buško, Vesna (Array, 2004)
The study aimed to examine the extent to which variations in measures of coping with specific low-control stressors are due to stable individual dispositions and/or to situational demands or occasion-specific factors. An inventory measuring three broad situation-specific coping dimensions, i.e., problem solving, acceptance of situation, and emotion-focused coping, was administered to 421 military trainees on two occasions five weeks apart. Several single-construct latent state-trait models were tested for each of the coping dimensions. The less restrictive versions of the latent state-trait models with unconstrained error variances and method factors proved to fit the data best for all three constructs. Parameter estimates obtained point to substantially higher consistency compared to the occasion specificity coefficients for each of the coping strategies analyzed. The proportions of variances attributable to occasion and/or interactional effects, however, showed to vary with a point of measurement and with the type of coping examined. Further, the analyses of the multi-construct models revealed significant within-occasion correlations of the latent state residuals of the three coping factors. The findings are discussed within the context of the latent state-trait theory and the processes of coping with continuously low-control stressful circumstances.